Integrated Band Intensities of Ethylene (C212H4) by Fourier Transform Infrared Spectroscopy. (28th August 2012) - Lebron, G. B.; Tan, T. L.
Abstract : The integrated band intensities of ethylene ( 12 C2 H4 ) in the 640–3260 cm −1 region were determined by Fourier transform infrared (FTIR) spectroscopy. The infrared absorbance spectra of the ν 7 and ν 10, ν 12, ν 7 + ν 8, ν 6 + ν 10, v 11, and ν 9 and ν 2 + ν 12 bands of ethylene recorded at a resolution of 0.5 cm −1 were measured at an ambient temperature of 296 K at various vapor pressures ranging from 3 × 10 − 5 to 1 × 10 − 3 atm to obtain respective Beer-Lambert's law plots. The measured integrated band intensities in cm −1 /cm atm were S ( ν 9 and ν 2 + ν 12 ) = 112.20 ± 0.24, S ( ν 11 ) = 55.35 ± 0.14, S ( ν 12 ) = 41.22 ± 0.30, and S ( ν 7 and ν 10 ) = 328.66 ± 16.55 . In addition, the measured infrared band intensities of the ν 7 + ν 8 and ν 6 + ν 10 combination bands of ethylene are reported for the first time: S ( ν 7 + ν 8 ) = 21.701 ± 0.028 cm −1 /cm atm and S ( ν 6 + ν 10 ) = 2.568 ± 0.025 cm −1 /cm atm.